Résistance Anti-Industrielle: Counterprojects - Lucien Steil (Journal of Traditional Building, Architecture and Urbanism)
This article discusses the role of “counterprojects” in architecture and urbanism as critiques of the industrialization and speculative development of urban spaces, particularly in the Brussels of the sixties and seventies. It highlights the contributions of Maurice Culot and Léon Krier, opposing the destructive modernization that was wiping out historic urban fabrics and displacing local communities. Their counterprojects aimed to revive traditional urbanism, emphasizing local craftsmanship, natural materials, and mixed-use neighborhoods and countering the sterile, high-rise developments that had come to dominate European cities. Some of these counterprojects exemplified this other vision, advocating for cities that prioritize human scale, social justice, and environmental sustainability. The author calls for the integration of these values into contemporary urban planning.